Structural styles and zircon ages of the South Tianshan accretionary complex, Atbashi Ridge, Kyrgyzstan: Insights for the anatomy of ocean plate stratigraphy and accretionary processes. (March 2018) - Sang, Miao; Xiao, Wenjiao; Orozbaev, Rustam; Bakirov, Apas; Sakiev, Kadyrbek; Pak, Nikolay; Ivleva, Elena; Zhou, Kefa; Ao, Songjian; Qiao, Qingqing; Zhang, Zhixin
Graphical abstract: Highlights: The lithotectonic assemblages are subdivided by the architecture into four units. The major structures and lithostratigraphy are thrusted duplexes and imbricated OPS. Detrital zircon ages demonstrating that are derived from the Ili-Central Tianshan Arc. The ages of the youngest components of the four units are P2, T1-2, C1 and T1 . South Tianshan ocean was subducted northward and closed in the P2 to T3 . The use of OPS should be based on detailed geological mapping. Abstract: The anatomy of an ancient accretionary complex has a significance for a better understanding of the tectonic processes of accretionary orogens and complex because of its complicated compositions and strong deformation. With a thorough structural and geochronological study of a fossil accretionary complex in the Atbashi Ridge, South Tianshan (Kyrgyzstan), we analyze the structure and architecture of ocean plate stratigraphy in the western Central Asian Orogenic Belt. The architecture of the Atbashi accretionary complex is subdivisible into four lithotectonic assemblages, some of which are mélanges with "block-in-matrix" structure: (1) North Ophiolitic Mélange; (2) High-pressure (HP)/Ultra-high-pressure (UHP) Metamorphic Assemblage; (3) Coherent & Mélange Assemblage; and (4) South Ophiolitic Mélange. Relationships between main units are tectonic contacts presented by faults. The major structures and lithostratigraphy of these units are thrust-fold nappes, thrusted duplexes, and imbricated ocean plate stratigraphy. All these rock units are complicatedly stacked in 3-D with the HP/UHP rocks being obliquely southwestward extruded. Detrital zircon ages of meta-sediments provide robust constraints on their provenance from the Ili-Central Tianshan Arc. The isotopic ages of the youngest components of the four units are Late Permian, Early-Middle Triassic, Early Carboniferous, and Early Triassic, respectively. We present a new tectonic model of the South Tianshan; a general northward subduction polarity led to final closure of the South Tianshan Ocean in the End-Permian to Late Triassic. These results help to resolve the long-standing controversy regarding the subduction polarity and the timing of the final closure of the South Tianshan Ocean. Finally, our work sheds lights on the use of ocean plate stratigraphy in the analysis of the tectonic evolution of accretionary orogens.